A Conceptual Innovative Risk Management Model for Commercial Buildings Refurbishment Projects - Masrom, Md. Asrul Nasid; Chan, Melissan; Ahamad, Junaidi (International Journal of Sustainable Construction Engineering and Technology, 2021)
Refurbishment concept has been recognized as an alternative for buildings that have reached the end of their service life or failed to perform as required. However, these types of projects is riskier and more complex than new construction projects. This is due to refurbishment projects involving a high level of uncertainty and requirements. As the size and complexity of refurbishment for commercial projects have increased, the ability to manage risks throughout the construction process has become a challenging task. To solve this, several risk-management tools are available, unfortunately, however, the tools are rarely used due to a lack of knowledge in selecting suitable techniques for refurbishment projects. Considering current scenario, a comprehensive tool to manage risks involved in refurbishment projects – particularly for commercial buildings – is necessary. A qualitative method of face-to-face interviews was used in the study. Content analysis showed that the proposed tool would be beneficial and pave a way to developers as risk management can influence their decision-making process.